Emissions from a Euro 6 engine using polyoxymethylene dimethyl ethers: Chemical effects vs mapping strategy. (1st March 2023) - Arias, Silvana; Agudelo, John R.; Ramos, Angel; Lapuerta, Magín
Highlights: Polyoxymethylene dimethyl ethers (OME3-5 ) were tested in a modern engine under WLTC. OME3-5 has shown to be a promising diesel fuel partial replacer. 20% OME blends led to 61% reductions in particle and 41% increases in NOx emissions. Oxygen content together with reduced EGR were the main reasons for these effects. Engine mapping strategy was shown to be an enhancer for chemical emissions effects. Abstract: New fuel technologies, such as electrofuels, are an attractive alternative to meet the energy demand and emission regulations, with sustainable electricity being the primary source of energy. Recently, there is increasing interest in using polyoxymethylene dimethyl ether (OME) as a diesel substitute. This study investigated the effect of a diesel fuel blend with 20% of OME (OME20) with 3–5 oxymethylene groups, on the performance, combustion characteristics, regulated emissions, particle number (PN), and particle size distribution in a compression ignition Euro 6 engine following the Worldwide harmonized Light vehicle Test Cycle (WLTC). Regulated emissions were measured downstream of the aftertreatment system, while PN emissions were measured upstream of the particulate filter. The results showed that OME20 increased the peaks of pressure and heat released rate, causing an increase in the combustion speed compared to diesel. OME20 reduced CO and THC accumulated emissions by 52% and 17%, respectively, and the PN exhibited a dramatic reduction close to 61%. Such reductions were influenced by both the fuel formulation and the engine settings induced by the fuel. With OME20, the engine requires higher fueling to maintain the same power output. Therefore, the accelerator pedal position was higher compared to diesel, leading a decrease in exhaust gas recirculation (EGR) rate to increase the air mass flow. Consequently, PN, CO and THC emissions were reduced, and conversely, accumulated NOx emissions increased up to 42%. OME20 decreased the peak number concentrations of accumulation-mode particles at all driving cycle phases and caused a slight shift of the particles toward smaller size compared to diesel fuel. From the results, it can be concluded that PN and regulated emissions, despite being strongly affected by the fuel properties, are very sensitive to the EGR rate and the equivalence ratio, which are established in the engine mapping.